TB Lipidomics—The Final Frontier - Chow, Eric D. (2011)
Lipids play critical roles in the biology of Mycobacterium tuberculosis, a notorious pathogen of man, but a systems-level approach to study these molecules have lagged behind other “omics” approaches. In this issue, Layre et al. describe the development of a powerful lipidomics technique and creation of a comprehensive database that address this need.